Peran Lsm Spektra Dalam Mutualism Partnership Program Bank Sampah - Aziza Nur Auliya; Erlinda Choirunnisa; Lukman Arif (Universitas Musamus, Merauke, Papua, 2020)
The rubbish is one of the environmental problems that is often highlighted as a national problem. The amount ofthe rubbish will increase in line with the high rate of population growth. Therefore, actors are needed to reducethese problems, one of which is NGOs. The purpose of this study was to determine how the role of the SPeKTRANGO in reducing waste problems through community empowerment with the garbage bank program. And to findout the SPeKTRA NGO partnership patterns, the government, civil society, and the private sector. The researchmethod used is descriptive-qualitative. Data obtained through interviews and documentation. Data analysistechniques used in this study are interactive data analysis with the stages of data reduction, data presentation,and drawing conclusions. The results showed that the role of the SPeKTRA NGO and the partnership establishedbetween the SPeKTRA NGO, the government, civil society, and the private sector through the garbage bankprogram had been well implemented. Based on the results of research analyzes in the field the role of theSPeKTRA NGO is carried out with reference to community welfare and service provision, education development,participation and empowerment, networking. While the partnership pattern is established through mutualismpartnership. Things that need to be improved are creativity and innovation by the SPeKTRA NGO in running thegarbage bank program and strengthening the role of each actor in running the partnership